Comparative Study of the Endocrine Disorders of Βeta-Thalassemia Major Patients and Control Group in Duhok Province - Ali, Ghorbat S.; Jubrial, Amad M.S.; Najeeb, Malika K.; Al hussein, Hamdia Y.I. (Science Journal of University of Zakho, 2018)
Beta- thalassemia major is a type of inherited blood disorder, characterized by impaired synthesis of the beta chains. Currently, blood transfusion and sufficient iron chelation therapy are important for treatment and follow up of thalassemia patients. Unfortunately, repeated blood transfusion causes the progressive iron overload. Consequently, the excess iron is deposited as hemosiderin and ferritin in the tissues and multiple endocrine complications. In comparison with healthy control group, the results indicated significant (p<0.05) increased TSH level (3.86 ± 2.7 1µIU/ml), whereas the serum level of T4 hormone did not significantly differ between the two groups. In the thalassemia patients, 23.68% (9/38) had subclinical hypothyroidism. The mean level of estradiol in patients (30.60± 14.68pg/ml) is high significant (p< 0.01) decreased that compared with the control persons (13.83 ± 9.06 pg/ml) more than 13 years. Testosterone level in patients was significantly different (P< 0.001) respectively from the control group. The mean of testosterone level was 1.22± 0.83 ng/ml in thalassemia patients and 3.71± 1.32ng/ml in control group more than 14 years. These results indicate high prevalence hypothyroidism and puberty defection. Endocrine drugs supplementation is a safe for patients which have each type of endocrine disorders.